Pengetahuan pasien tentang obat antihipertensi dalam pencegahan kegawatdaruratan hipertensi - Bintang Almuharam; Shinta Arini Ayu; Sri Kurnia Dewi (Holistik Jurnal Kesehatan, 2026)
Background: Hypertension is a chronic disease with a high prevalence and carries a risk of serious complications, including hypertensive emergencies. A crucial factor in hypertension management is patient knowledge of antihypertensive medications. Lack of understanding of their function, dosage, side effects, and adherence to treatment can lead to non-adherence to therapy and an increased risk of complications. Purpose: To determine the level of knowledge about antihypertensive medications among hypertensive patients as a preventative measure against hypertensive emergencies. Method: This is a quantitative descriptive study with a cross-sectional approach. The study was conducted in Sindanglaya Village, within the Cipanas Community Health Center (Puskesmas), Cianjur Regency, from January to February 2026. A sample of 79 respondents was selected using a purposive sampling technique. Data were collected using a questionnaire on antihypertensive medication knowledge consisting of five domains, then analyzed univariately using frequency distributions. Results: The level of knowledge of hypertensive patients across all domains was relatively low. The percentage of correct answers in the domain of drug function and purpose was 39.87%, instructions for use and dosage 32.70%, types and mechanisms of drug use 33.92%, side effects and risks 31.65%, and compliance and complication prevention 29.87%. The domain of compliance and complication prevention was the domain with the lowest level of knowledge. Conclusion: Hypertensive patients' knowledge of antihypertensive drugs remains suboptimal across all domains. This indicates that patient understanding of drug therapy still needs to be improved. Therefore, more targeted, sustainable, and easily understood educational efforts tailored to patient characteristics are needed to support successful therapy and prevent complications of hypertension.   Keywords: Antihypertensive Drugs; Hypertensive Emergencies; Knowledge.